2021
DOI: 10.3389/fphar.2020.621835
|View full text |Cite
|
Sign up to set email alerts
|

Inonotus obliquus Polysaccharide Ameliorates Azoxymethane/Dextran Sulfate Sodium-Induced Colitis-Associated Cancer in Mice via Activation of the NLRP3 Inflammasome

Abstract: Inonotus obliquus polysaccharide (IOP), the primary constituent of the parasitic fungus Inonotus obliquus, has anti-tumor, anti-inflammatory, anti-oxidation effects. However, the roles of IOP on colitis-associated cancer (CAC) are still unclear. Herein, we tested the efficacy of IOP using a mouse model of CAC induced by azoxymethane and dextran sulfate sodium (AOM/DSS). We confirmed that intragastric administration of IOP decreased CAC-induced body weight loss, colon tissue damage, colon shortening, and expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Besides, Jiang’s research demonstrated that IOPS could significantly inhibit allograft tumor growth of the LLC1 cells with increased apoptosis at 50 mg/kg dosage [ 100 ]. Li tested the efficacy of IOPS by using a mouse model of Colitis-Associated Cancer (CAC) induced by azoxymethane and dextran sulfate sodium (AOM/DSS) to confirm that IOPS inhibited the proliferation of SW620 colorectal cancer cells [ 22 ].…”
Section: Biological Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, Jiang’s research demonstrated that IOPS could significantly inhibit allograft tumor growth of the LLC1 cells with increased apoptosis at 50 mg/kg dosage [ 100 ]. Li tested the efficacy of IOPS by using a mouse model of Colitis-Associated Cancer (CAC) induced by azoxymethane and dextran sulfate sodium (AOM/DSS) to confirm that IOPS inhibited the proliferation of SW620 colorectal cancer cells [ 22 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…When the activation of NLRP3 inflammasome is inhibited, the inflammation-related diseases involved in it may be improved. In Lipopolysaccharide (LPS)-induced macrophage inflammation, Zheng found that IOPS can inhibit the expression of IL-18 and IL-1β by inhibiting the phosphorylation of NF-κB-p65 ( p < 0.05) [ 22 , 138 , 139 ].…”
Section: Biological Activitymentioning
confidence: 99%
See 3 more Smart Citations